Developing an attractant for monitoring fruit-feeding moths in citrus orchards - Goddard, Mathew Keith (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Fruit-piercing moths are a sporadic pest of citrus, especially in the Eastern Cape Province of South Africa, where the adults can cause significant damage in outbreak years. Currently the only way in which to successfully control fruit-feeding moths within the orchards is the use of repellent lights. However, growers confuse fruit-piercing moths with fruit-sucking moths that don't cause primary damage, and there is no way of monitoring which moth species are attacking the fruit in the orchards during the night. In a previous study, banana was shown to be the most attractive bait for a variety of fruit-feeding moth species. Therefore the aim of this study was to determine the population dynamics of fruit-feeding moths develop a cost-effective alternative to the use of fresh banana as a bait for fruit-piercing moths. Fresh banana was compared to nine alternative synthetic attractants, frozen banana and a control under field conditions in several orchards in the Eastern Cape Province. Once again, banana was shown to be the most attractive bait. Some 23 species of fruit-feeding moth species were sampled in the traps, but there was only two fruit-piercing species, Serrodes partita (Fabricius) (Lepidoptera: Noctuidae) and Eudocima sp. Surprisingly S. partita, which was thought to be the main pest, comprised only 6.9% of trap catches. Serrodes partita, is a sporadic pest, only becoming problematic every five to 10 years after good rainfall in the Little Karoo region that causes flushes of their larval host, wild plum, Pappea capensis (Ecklon and Zeyher). During these outbreaks, damage to fruit can range from 70 to 90% and this is especially so for soft skinned citrus. A study on the morphology of the proboscis confirmed that only two species of fruit-piercing moths were present. Trap catches over three citrus growing seasons was linked to fruit damage found within several orchards. Once again fruit-piercing moth damage was relatively low in comparison to other types of damage such as mechanical and undefined damage. There was a very weak correlation between S. partita trap catches and damage, but generally damage was recorded two to three weeks after a peak in S. partita trap catches. Climatic conditions were also recorded and compared to weekly trap catches of S. partita, and while temperature and wind direction had no influence on moth populations, precipitation in the orchards was weakly correlated with trap catches. This study has shown that in non-outbreak seasons, the main fruit-piercing moth, S. partita comprises a small percentage of fruit-feeding moths in citrus orchards, but that growers are unable to determine the difference between fruit-piercing species and the harmless fruit-sucking species. Further fresh banana remains the best method for attracting fruit-piecing moths to traps, but this is not cost effective and thus a commercially viable protocol for monitoring these species remains elusive.
Keywords: Uncatalogued